Characterization of Vancomycin Resistant Enterococci Isolated from Retail Poultry Meat - El-Oraby, Sara; Awad, Amal; Younis , Gamal (Journal of Advanced Veterinary Research, 2023)
Antimicrobial-resistant bacteria in poultry meat threaten the public health.Â The present study was designed to detect the presence of Enterococcus species in poultry meat collected from Mansoura retail outlets with characterization of vancomycin-resistant enterococci (VRE). Thus, poultry meat samples (breast and thigh) were collected from separate grocery stores around Mansoura city, Egypt. By conventional and molecular methods, out of the total examined samples (n=120), 44 E. fecalis isolates have been recovered with a percentage of 36.66%. All strains were assessed for their antimicrobial susceptibility using disc diffusion method, the highest rate of resistance (100%; 44/44) was displayed to ceftazidime, streptomycin, gentamycin, and clindamycin, while, a resistance rate of 36.3%, 40.9%, 68.1% and 77.2% were displayed against ciprofloxacin, penicillin, erythromycin and vancomycin respectively. Interestingly, all isolates exhibited multidrug resistance (MDR; Resistance to three or more antimicrobial class). Screening vancomycin -resistant strains (n= 34) by PCR for the presence of vancomycin resistance genes, vanA was identified in 47.1% vanB in 33.4%, vanC1 in 14.7% and vanC-2 C-3 in 5.9%. By testing the ability of the isolated strains for the biofilm production by Congo Red Method, 31.8 % of the tested isolates were tested positive. Hence, standard manufacturing procedures and adequate hygiene conditions must be integrated into all phases of poultry meat preparation, production and consuming, and public knowledge should be improved.